Applying rhythm teaching methods in an instrumental ensemble - Quilling, Michael Lance (Kansas State University, 2017)
Finding a systematic process for teaching rhythms in the instrumental setting has presented its own set of challenges. Numerous factors such as time constraints, engagement, motivation, and various degrees of proficiency amongst the students can all play a part in the overall success of the group. This video presentation includes a teaching demonstration utilizing techniques acquired from MU680-A (Advanced Rehearsal Techniques). Using rhythm readiness sheets modeled by Dr. Jay Gilbert and specific rehearsal techniques taught by Dr. Frank Tracz, this presentation exhibits a process for teaching rhythms that increases retention of rhythmic patterns in a way that enables all students to engage in the learning process simultaneously. The lesson plan is explained in detail and the routine was repeated daily and eventually implemented into the twelve-minute warmup portion of the rehearsal. After three weeks the students were recorded and asked to reflect on their progression. A noticeable change was observed after the lesson was completed and applied to the piece. In addition, the method also revealed several hidden learning outcomes, such as facilitating independence as musicians, utilizing listening skills to distinguish how various patterns fit within an established pulse, and increasing student motivation by creating positive rehearsals with attainable goals. The result was a performance showcasing the growth of the ensemble’s overall musicianship. The rhythm readiness sheet and concept that was utilized in the teaching demonstration is credited to Dr. Jay Gilbert. The rhythm readiness sheet is not copyrighted or published, however expressed written consent was granted by Dr. Gilbert and can be found in the Appendix.
Keywords: Rhythm counting techniques for instrumental ensembles